External dacryocystorhinostomy with bicanalicular intubation – retrospective analysis of results and complications - Lemos, José Alberto (2015)
Purpose: To evaluate surgical success rates and complications in patients with acquired nasolacrimal duct obstruction that underwent external dacryocystorhinostomy (DCR) with bicanalicular intubation.  Methods: 63 external DCR’s performed in 58 patients were retrospectively evaluated. The variables analyzed were: age, gender, initial signs and symptoms, complications, surgical success rate and reoperations. Surgical success was defined by the presence of anatomical patency associated with resolution of epiphora (full success) or improvement of epiphora (partial success). All cases with persistent epiphora without anatomical patency or cases of recurrent dacryocystitis were classified as unsuccessful. Results: Patients mean age was 63.13 years, with female predominance (84.5%). Epiphora was the most frequent initial symptoms (71.4%). Of the 63 surgeries, fifty-five were first interventions and 8 were reoperations. Intraoperative and postoperative complications were unusual. In the postoperative complications, we must emphasize those related with silicone tube, with 3 cases of tube prolapse and 2 case of early tube extrusion. Surgery was unsuccessful in 6 cases (9.5%). Conclusions: Surgical success rate (full + partial) with external DCR was 90,5%. This surgical technique is a great option in the treatment of nasolacrimal duct obstructions, with high surgical success rates and low rate of complications. However, intraoperative intubation is not free of complications.